Study on factors that affect employee retentions and turnovers in Vista Point Technologies (Malaysia) Sdn. Bhd. / Mohamad Solehuddin Shah Ismail - Ismail, Mohamad Solehuddin Shah (Faculty of Business and Management, 2009)
This research is conducted to study the effectiveness factors that affecting employee retentions and turnover in Vista Point Technologies (M) Sdn. Bhd. While much research has been conducted on these three variables separately, very little has been done in terms of understanding the relationship between them. This research aims to examine the impact of all this effectiveness factors that affecting employee retention and turnover in Vista Point Technologies (M) Sdn. Bhd. The effectiveness factors including financial rewards, career perspectives and work environments refers to employee retentions and turnovers in the organizations, and how these relations influence the employees well-being, behavior, and job satisfactions to the organization. In obtaining employees opinion towards this issue, researcher has distributed 50 questionnaires to the respondents and only 50 usable questionnaires were returned. Researcher used the Statistical Packages for social Sciences (SPSS) version 16 to analyze all data. The data was analyzed using Reliability test, Descriptive analysis, and Pearson’s correlation analysis. The result shows that the effectiveness factors that affecting has significant relationships with employee retentions and turnovers. All of this is based on the findings through the questionnaire been distributed for this study.